Favorite horses breeds girls love - Kolpin, Molly (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2014)
"Photos and text introduce readers to different horse breeds, including specific breed characteristics, features, and origins"--
Breed basics -- All-American classics -- Lightning-fast thoroughbreds -- Patterned beauties -- Heavy lifters
Science (Animals)
Includes bibliographical references (page 31) and index
Ages 8-14
Grades 4 to 6
1 2 13
Keywords: Horse breeds -- Juvenile literature; Horses -- Juvenile literature